Business Statistics / Study Guide Basic Concepts and Methodology: Fourth Edition - Daniel Wayne W; Terrell James C (Houghton Mifflin Company, 1986)
Preface, The Role of Statistics in Decision Making, Organizing and Summarizing Data, Some Elementary Probability Concepts, Some Important Probability Distributions, Some Important Sampling Distributions, Statistical Inference I: Estimation, Statistical Inference II: Hypothesis Testing, Analysis of Variance, Simple Linear Regression and Correlation, Multiple Regression and Correlation, The Chi-Square Distribution and the Analysis of Frequencies, Nonparametric Statistics, Time-Series Analysis and Forecasting, Elementary Survey Sampling, Statistical Decision Theory, Some Statistical Applications in Quality Control.